Modeling and simulation for supply chain finance under uncertain environment - Jin, Wei; Wang, Chengfu (Technological and Economic Development of Economy, 2020)
This paper studies the role of factoring in a bilateral supply chain, where both the supplier and retailer are financially constrained. Applying the stylized Stackelberg game, we analytically present that the supplier’s capital shortage limits the advantage of trade credit provided to the retailer. To overcome this limitation, we design a hybrid strategy composing of trade credit and factoring, and then investigate how the supplier uses factoring strategy to achieve the best performance. Analytical and numerical results show that: (1) each supply chain partner can benefit from factoring, and the benefits depend on operational and financial characteristics; (2) in a fairly priced factoring market, bankruptcy costs reduce the benefits of factoring, but does not change the dominance of full factoring; (3) in a strategically priced factoring market, partial factoring may dominate full factoring. Managerially, our study implies that a supplier may benefit from dividing his accounts receivable when facing a factor with a strong pricing ability.First published online 28 February 2020